Firm Life Cycle Stage and Dividend Payout of Listed Non-Financial Firms in Selected Sub-Saharan African Countries: A Sectoral Analysis - Omoruyi Aigbovo; Ikavbo Esther Evbayiro-Osagie (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
This study explored the sector-wise effect of firm life cycle stage on dividend payout of listed non-financial firms in three selected Sub-Saharan African countries that include; South Africa, Nigeria, and Kenya, utilizing the dynamic panel data regression technique - system generalized method of moments (system GMM) for the period 2007 to 2017. The outcomes of the empirical analysis revealed that the earned/contributed capital mix exerts a direct and significant effect on payout of dividend in seven out of the 10 subsectors analyzed while firm age exerts an inverse and significant effect on payout of dividend in six out of the 10 subsectors analyzed. The study recommended among others that stock market regulators in the selected Sub-Sahara Africa countries should consider the life cycle stage of the firms and the earned/contributed capital mix should be used in measuring the maturity of firms, thus payment of dividend by firms should be based on when its profitability and growth rate are expected to fall in future.